2009
DOI: 10.1111/j.1445-2197.2008.04828.x
|View full text |Cite
|
Sign up to set email alerts
|

E‐Learning in surgical education and training

Abstract: For most surgeons and surgical educators, e-learning is relatively new and confusing. This article attempts to explain the key concepts behind e-learning, as well as its benefits and risks. E-learning has become a fixed feature within Higher and Professional Education and has been prioritized by Universities around the world, as well as all six Surgical Royal Colleges. Trainees have grown up with virtual learning environments and expect similar provision for their postgraduate studies, but have a greater need … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
33
0
5

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 73 publications
(38 citation statements)
references
References 5 publications
(7 reference statements)
0
33
0
5
Order By: Relevance
“…Findings related to learner preference are inconsistent. In some cases the surveyed population preferred classroom learning due to issues such as teacher-student interaction (1), but in other cases they preferred online learning due to the uniformity of the learning experience (5) and the flexibility and convenience of this approach (6, 7). Although the research findings provide significant support for online learning as an effective pedagogical method, researchers warn that appropriate instructional design and easy-to-access technology are both key to effective outcomes (8, 9).…”
mentioning
confidence: 99%
“…Findings related to learner preference are inconsistent. In some cases the surveyed population preferred classroom learning due to issues such as teacher-student interaction (1), but in other cases they preferred online learning due to the uniformity of the learning experience (5) and the flexibility and convenience of this approach (6, 7). Although the research findings provide significant support for online learning as an effective pedagogical method, researchers warn that appropriate instructional design and easy-to-access technology are both key to effective outcomes (8, 9).…”
mentioning
confidence: 99%
“…[19][20][21][22][23][24][25][26] Four publications from surgical professional bodies are found. 26,27,28,29 Table 1 gives the breakdown of sample size in individual papers within our study population. Sample size information was present in 17 studies, to give a total of 1474 predominantly surgical professionals.…”
Section: Resultsmentioning
confidence: 99%
“…Supplemental clinical photographs and operative images gave contextual motivation for plain text. Refocussing on our research sample, amongst the 12 studies with multimedia tool provision, only 4 studies 22,24,28,39 (33%) demonstrated the nuances described by Choi. 48 The web design by Friedl 24 is an excellent example of this with the ability to mark on the cardiac surgical image or animation, which corresponds to an intraoperative step.…”
Section: Multimediamentioning
confidence: 90%
See 2 more Smart Citations